Denoising of dual-VENC PC-MRI with large high/low VENC ratios - Brunátová, Jana; Löcke, Miriam; Uribe, Sergio; Bertoglio, Cristóbal (Magnetic resonance in medicine, 2025)
PURPOSE: Dual velocity encoding PC-MRI can produce spurious artifacts when using high ratios of velocity encoding values (VENCs), limiting its ability to generate high-quality images across a wide range of encoding velocities. This study aims to propose and compare dual-VENC correction methods for such artifacts. THEORY AND METHODS: Two denoising approaches based on spatiotemporal regularization are proposed and compared with a state-of-the-art method based on sign correction. Accuracy is assessed using simulated data from an aorta and brain aneurysm, as well as 8 two-dimensional (2D) PC-MRI ascending aorta datasets. Two temporal resolutions (30,60) ms and noise levels (9,12) dB are considered, with noise added to the complex magnetization. The error is evaluated with respect to the noise-free measurement in the synthetic case and to the unwrapped image without additional noise in the volunteer datasets. RESULTS: In all studied cases, the proposed methods are more accurate than the Sign Correction technique. Using simulated 2D+T data from the aorta (60 ms, 9 dB), the Dual-VENC (DV) error 0 . 82 ± 0 . 07 $$ 0.82± 0.07 $$ is reduced to: 0 . 66 ± 0 . 04 $$ 0.66± 0.04 $$ (Sign Correction); 0 . 34 ± 0 . 04 $$ 0.34± 0.04 $$ and 0 . 32 ± 0 . 04 $$ 0.32± 0.04 $$ (proposed techniques). The methods are found to be significantly different (p-value < 0 . 05 $$ <0.05 $$ ). Importantly, brain aneurysm data revealed that the Sign Correction method is not suitable, as it increases error when the flow is not unidirectional. All three methods improve the accuracy of in vivo data. CONCLUSION: The newly proposed methods outperform the Sign Correction method in improving dual-VENC PC-MRI images. Among them, the approach based on temporal differences has shown the highest accuracy.
Keywords: Magnetic Resonance Imaging; aorta; mozek; magnetická rezonanční tomografie; Humans; Algorithms; Phantoms, Imaging; Computer Simulation; interpretace obrazu počítačem; Artifacts; artefakty; lidé; denoising; počítačové zpracování obrazu; Image Processing, Computer-Assisted; reprodukovatelnost výsledků; poměr signál - šum; Image Interpretation, Computer-Assisted; Signal-To-Noise Ratio; počítačová simulace; Reproducibility of Results; Brain; algoritmy; intrakraniální aneurysma; dual‐VENC; phase‐contrast MRI; fantomy radiodiagnostické; Aorta; Intracranial Aneurysm